Publishing in the Digital Era: Open Access Journals Model - Gaffar Ali, Abdelrahim Mutwakel (مجلة الجزيرة للعلوم الصحية; مجلد 13 عدد 1 (2017), 2017)
The Directory of Open Access Journals (DOAJ) was launched in 2003 at Lund University, Sweden.DOAJ is a membership organization, Publisher, Ordinary Member and Sponsor are the three membership available categories. It is a community-curated list of open access journals and aims to be the starting point for all information searches for quality, peer reviewed open access material. Membership in the DOAJ is a vibrant declaration of intent and proves a commitment to quality, peer-reviewed open access. To support Open Access Journals (OAJ) community, DOAJ is co-author to the Principles of Transparency and Best Practice in Scholarly Publishing (Principles) (https://doaj.org/bestpractice) and DOAJ members are expected to pursue these principles as a condition of membership.